Impacts of meloxicam administration before temporary calf weaning on physiological and reproductive responses of Bos indicus beef cows - Cooke, R. F. (2016)
The objective of this experiment was to evaluate temperament, physiological, and reproductive variables in Bos indicus beef cows assigned to an estrus synchronization + timed AI protocol including eCG administration, 48-h temporary calf weaning (TCW), or TCW + meloxicam administration. A total of 943 lactating, multiparous, nonpregnant Nelore cows, allocated into 8 groups of approximately 120 cows each, were assigned to the experiment. Groups were maintained in individual pastures and assigned to the following estrus synchronization + timed AI protocol: a 2-mg injection of estradiol benzoate and an intravaginal progesterone-releasing device (CIDR) on d 0, a 12.5-mg injection of PGF(2 alpha) on d 7, CIDR removal in addition to a 0.6-mg injection of estradiol cypionate on d 9, and timed AI on d 11. Within each group, cows were randomly assigned on d 9 to 1) TCW from d 9 to 11 (TCW-CON; n = 317), 2) no TCW and a 300-IU injection of eCG on d 9 (NOTCW; n = 311), and 3) TCW-CON in addition to meloxicam administration (intramuscular; 0.5 mg/kg BW) on d 9 (TCW-MEL; n = 315). Cow BW and BCS were assessed on d 0. On d 9 and 11, blood samples were collected, and cow temperament was evaluated via chute score and exit velocity. Pregnancy status was verified 30 d after timed AI via transrectal ultrasonography. No treatment differences were detected (P >= 0.23) for cow age, days postpartum, BW, and BCS on d 0 of the estrus synchronization + timed AI protocol. No treatment effects were detected (P >= 0.41) for any of the temperament variables evaluated. A treatment x day interaction was detected (P = 0.02) for serum cortisol concentrations, which were similar (P = 0.55) between treatments on d 9 but greater (P <= 0.05) in TCW-CON and TCW-MEL compared with NOTCW cows on d 11. No treatment effects were detected (P = 0.90) for serum haptoglobin concentrations, which decreased from d 9 to 11 in all treatments (day effect; P < 0.01). No treatment differences were detected (P = 0.84) for pregnancy rates to timed AI. In summary, TCW during estrus synchronization did not impact temperament or serum haptoglobin concentrations in B. indicus beef cows but increased serum cortisol concentrations compared with cows not assigned to TCW, although such an outcome was not sufficient to impact pregnancy rates to timed AI. Moreover, administration of meloxicam did not alleviate the TCW-induced increase in serum cortisol concentrations and failed to benefit pregnancy rates to timed AI in B. indicus beef cows.